Diagnóstico de distemper canino en animales con síntomas de la enfermedad en Machala - Castro Córdova, Luis Alberto (2011)
The investigation was carried out in Machala city, El Oro county, during the months from May to December of the 2008 the objectives were: 1.- To diagnose Canine Distemper in animals with moquillo symptoms in Machala city; 2.- To determine the percentage of infection of the same one; 3.- To establish the distribution among race, age, sex and origin. The diagnoses were made with the quick supporting card Anigen for antigen of canine Distemper. The animal was sampled in number of 100 that presented suspicious symptoms of the illness (moquillo), or with symptoms of breathing illnesses. Most of the cases were animal taken to consultation to the collaborating clinics, giving a rate of high infection as a result. They were not differences of positive among sex, age and race, the biggest percentage of positive was determined in the urban sector.